Isoterma dan Termodinamika Adsorpsi Kation Cu2+ Fasa Berair pada Lempung Cengar Terpilar - Bahri, Syaiful; Muhdarina, Muhdarina; Nurhayati, Nurhayati; Andiyani, Fitri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
Pillared Cengar clay have been synthesized by two methods, first clay suspension is directly mixed into aqueous solution of hydroxy-aluminum polycations (WK) and second by mixing the clay suspension into the solution of sodium acetate and hydroxy-aluminumpolycations (SAK) sequentially. Both clays were calcined in air on atmospheric condition. Diffraction pola, surface morphology and cationexchange capacity of the pillared clays were characterized using X Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) andvisible spectrophotometry methods, respectively. The pillared clays showed increases of basal spacing from 3.57 Å to 4.55 Å and smectiteas a new mineral. Morphology of SAK has more heterogeneous surface with small plates and agglomeration of grains compare with WKwhich small plates. Adsorption of aqueous cation of Cu 2+ were studied on various variables of initial concentration as well as temperatures.As the result, adsorption of cation Cu 2+ on pillared Cengar clay is corresponding to Freundlich isotherm, while the adsorption capacity ofWK on cation Cu 2+ is slightly lower than SAK. The thermodynamic aspect, the WK is reflected possessed exothermic processes withnegative entropy, increased in Gibbs energy and non spontaneous, while the SAK possessed endothermic processes having positive entropy,decreased in Gibbs energy and non spontaneous.